ORIF (Open Reduction and Internal Fixation) of the Zygomatic Arch Fracture Using Transbuccal Instrumentation - Hiralal Ash; Kumar Arunesh; Rajeev K. Singh; Ajay K. Singh; Sujay K. Sinha; Abhishek K. Singh (Journal of Pharmacy and Bioallied Sciences)
Background: The zygomatic arch fracture indicated using ORIF (open reduction and internal fixation) after its fracture in a few clinical scenarios. Aim: To assess the efficacy of ORIF (open reduction and internal fixation) for zygomatic arch fracture using transbuccal instrumentation. Method: The study assessed 60 subjects who needed ORIF of the zygomatic arch fracture, and reduction was done following transbuccal instrumentation under general anesthesia. Various clinical parameters were assessed, including mouth opening, swelling, and aesthetic outcomes in the preoperative and postoperative periods of 1 week, 1 month, and 3 and 6 months. Results: Among 60 subjects assessed, aesthetic restoration and satisfactory anatomical reduction were seen in 93.3% (n = 56) of study subjects, whereas 6.7% (n = 40) of subjects needed revision surgery owing to the displacement of the plate. Mean postoperative mouth opening showed improvement from 20 mm to 40 mm in the three-month follow-up. Minimal postoperative swelling subsided in 95% of subjects by first month of assessment. Four patients experienced mild temporary paresthesia in the infraorbital nerve which was resolved in 3 months. No infections or other complications were seen during the study period. Conclusion: Intraoral open reduction and internal fixation using transbuccal fixation is a less invasive, effective, and simple method to manage the fractures of the zygomatic arch with no associated complications and acceptable outcomes concerning swelling, mouth opening, and aesthetics.